Hemangiossarcoma multicêntrico em medula espinhal de cão - Santos, Paulo Victor Braga de Almeida (2019)
Hemangiosarcoma (HSA) is one aggressive malignant neoplasm of mesenchymal origin that can arise in a single site, reach several organs and develop metastases or present in a way multicentric. The approach of this study is a10-year-old male canine that was eneterected the sectors to the emergency department of the Federal University of Mato Grosso, with dyspnea, outpatient tetraparesis, cyanosis and ataxia. 27 days before emergency care, the animal underwent a surgical procedure of breast tumor excision with diagnosis of breast adenocarcinoma. The animal underwent a procedure of blood collection and radiographic examination, where the dyspnea intensified. Anemia and leukocytosis were demonstrated on blood test. Radiography showed radiopaque nodules with multifocal distribution through the pulmonary parenchyma, suggesting metastatic neoplasia and fungal infection, hours later the dyspnea intensified and the animal died. Histopathological analysis showed blackish multifocal areas of 0.4 cm in diameter in the brain, in a parietal cortex region with spinal cord involvement. The patient described here presented neurological signs that refer to hemangiosarcoma involvement in different anatomical levels of the central nervous system.